Poisoning in puppy dog after accidental ingestion of printing ink: Case report - Gomes, Pedro Eduardo Bitencourt; Carvalho Filho, João de Deus; Machado, Gildene Fortes de Meneses; Lemos, Jane Gabriela Soares de; Gomes, Lucélia Keila Bitencourt; Pereira, Geilson Silva; Amaral, Dariely de Carvalho Monte; Silva, Acácio Costa (Pubvet, 2022)
Several cases of exogenous poisoning in pets or wild animals are treated in veterinary clinics and hospitals each year. Whether accidental or intentional, they occur mainly in the domestic environment and are associated with various toxic substances. The present study aimed to report a case of exogenous intoxication in a 4-month-old female German shepherd dog after accidental ingestion of printing ink. To aid and develop this work, an integrative literature review study was also used to list the main heavy metals that make up the pigments and structure of printer cartridges: arsenic, barium, cadmium, lead, chromium, silver and selenium, their respective mechanisms of action and clinical signs in intoxicated animals. In that report, topics were included about the initial clinical picture, the clinical procedure performed with the patient, the anamnesis, the therapy (Ornitil, Ringer Lactate and Furosemide), the evolution of the case and the discharge of the patient with guidance to the tutor. The databases established for the research were BVS, PubMed and Google Scholar from March to June 2022. The work was a case report, in which the databases established for the research were BVS, PubMed and Google Scholar from March to June 2022. The descriptors used were cão (dog), intoxicação (intoxication) and tinta (ink), with a defined time frame from 2000 to 2020.